Influence of Local Sand on the Physicomechanical Comportment and Durability of High Performance Concrete - Nadia Tebbal; Zine El Abidine Rahmouni (Advances in Civil Engineering)
This research consists of incorporating the crushed sand (CS) in the composition of a concrete and studies the effect of its gradual replacement by the sand dune (SD) on sustainability of high performance concrete (HPC) in aggressive environments. The experimental study shows that the parameters of workability of HPC are improved when the CS is partially replaced by the SD (<2/3). However, a high content of SD (>1/3) additional quantities of water is needed to meet the workability properties. The mechanical strengths decrease by adding the SD to CS, but they reach acceptable values with CS in moderate dosages. The HPC performances are significantly better than the control concrete made up with the same aggregates. The specification tests of durability show that the water absorbing coefficients by capillarity increase after adding SD to the CS.